[PP.25.12] AMBULATORY BLOOD PRESSURE MONITORING-DERIVED SHORT-TERM BLOOD PRESSURE VARIABILITY IN PRIMARY HYPERPARATHYROIDISM. (September 2016) - Concistre', A.; Grillo, A.; Carretta, R.; Fabris, B.; Petramala, L.; Marinelli, C.; Rebellato, A.; Fallo, F.; Letizia, C.
Abstract : Objective: Primary hyperparathyroidism (PHPT) is associated with a cluster of cardiovascular manifestations, including hypertension, leading to increased cardiovascular risk. The aim of our study was to investigate the ambulatory blood pressure monitoring (ABPM)-derived short-term blood pressure variability (BPV) in patients with PHPT, in comparison with patients with essential hypertension and normotensive controls. Design and method: Twenty-five patients with PHPT (7 normotensive, 18 hypertensive) underwent ABPM at the time of diagnosis, and fifteen out of them were re-evaluated after surgical parathyroidectomy. Short-term BPV was derived from ABPM and calculated as the following: (1) Standard Deviation (SD) of 24-h, daytime and nighttime BP; (2) the average of daytime and night-time SD, each weighted for the duration of the day and night periods (24-h "weighted" SD of BP); (3) average real variability (ARV), i.e., the average of the absolute differences between consecutive BP measurements over 24 hours. Baseline data were compared with 11 normotensive and 22 hypertensive controls matched for age, sex and mean BP. Results: Normotensive PHPT patients showed a higher systolic weighted SD than that of normotensive controls (11.52 ± 3.50 vs 8.50 ± 1.29, p = 0.01). Other measures of BPV where not significantly different between normotensive and hypertensive PHPT patients, nor between hypertensive PHPT and hypertensive controls. Systolic ARV, as well as serum parathyroid hormone (PTH) and calcium levels, were significantly reduced in surgically operated patients (sysARV: 8.77 ± 0.85 vs 7.51 ± 1.28 p = 0.01, PTH (pg/ml): 126.3 ± 56.7 vs 52.9 ± 24.9, p < 0, 001; Ca (mg/dL): 11.38 ± 1.13 vs 9.14 ± 0.52, p < 0, 001). Conclusions: Systolic BPV is increased in normotensive patients with PHPT and normalized after surgical parathyroidectomy. A direct pathogenic role of increased serum PTH and/or calcium levels in altering this feature could be hypothesized in this disease.